P‐26: Reconstruction of Wide Range Exposures and Diverse High Dynamic Range Image Styles for Displays. Issue 1 (30th May 2018) - Soh, Jae Woong; Park, Jae Sung; Cho, Nam Ik
Abstract : This paper presents a high dynamic range (HDR) imaging method, which generates virtual wide range exposures and diverse HDR tone styles from a single exposure image. Wide range exposures are generated by the illumination transform function that estimates and adjusts the illumination component of an input image. To visualize various styles of HDR images on HDR displays, the dynamic ranges of the wide range exposures are expanded by employing our exposure‐dependent brightness enhancement function (EBEF) which is adaptive to the virtual exposure values.